Chemical Profiles of Industrial Cow's Milk Curds - Barone, Caterina; Barbera, Marcella; Barone, Michele; Parisi, Salvatore; Steinka, Izabela (Chemistry of Foods, 2017)
This Brief explores the chemistry and production technology of a cheese precursor: the cow's milk curd. It explains how different coagulation and treatment methods can be used to obtain various types of cheeses. Parameters such as the type of used milk, the coagulation method, pH value, color, and microbial fermentation have a profound impact on the resulting curd properties, and hence on the cheese. The authors discuss some of the most important parameters, and how their modification can lead to a variety of cheese and dairy products. This Brief also addresses the question, if cheese makers can standardize their production procedures, and what role chemistry may play in that. Another important point addressed here are the sources of failures in the curd production, e.g. in packaging systems. Readers will find selected examples of helpful analytical techniques for studying and evaluating curd quality, and for monitoring the chemical evolution of selected chemical substances or protein aggregation. .